Stage It and Stream It: Plays for Virtual Theater - Bray, John Patrick (Rowman & Littlefield Publishers, 2023)
Playwrights have always demonstrated an incredible adaptability, able to nimbly adjust to new circumstances and media. This was never in greater evidence than during the coronavirus pandemic, when—with venues shuttered and stages darkened—writers and performers across the world scrambled to sustain the art of theater via remote video. Even today, it is clear that the experiences of 2020–21 have dramatically altered the landscape of theatermaking, as artists continually refine and deploy the lessons learned during a period of seat-of-the-pants experimentation. This groundbreaking anthology brings together new works from both emerging and established playwrights to explore the rich opportunities afforded by streaming theater. They reveal a range of styles and approaches to storytelling; encompass both traditional and experimental plays, from solo pieces to large-cast dramas; and take place within single settings, multiple settings, or even in a utopian “nowhere.” Throughout, these selections all help to bring playwriting fully into our new era, embodying the sense of magic that comes from simple moments of human connection, even when we cannot be together. Includes plays by the following: Audrey Cefaly Joyce Miller J. Merrill Motz Arlene Hutton Greg Lam Vince Gatton Lindsay Adams Sharece M. Sellem Mrinalini Kamath Brendan Powers and Rachel Burttram Dana Hall Aly Kantor Kitt Lavoie Jenny Lyn Bader Ivam Cabral and Rodolfo García Vázquez Michael Hagins Trey Tatum with Jordan Trovillion Colette Mazunik Tory Parker Eric Eidson and Lauren Lynch-Eidson